The Dominican Republic–Central American Free Trade Agreement's Symbolic Nod to Environmental Protection: Legal Perspectives on the Citizen Submission Process. Issue 10 (3rd October 2017) - Upton, J. Christopher; Tucker, Catherine M.; Sanchez, Seleste
ABSTRACT: The Dominican Republic–Central America Free Trade Agreement (CAFTA) contains a chapter on the environment, ostensibly included to mitigate the North American Free Trade Agreement (NAFTA) environmental oversights. The environment chapter created a citizen submission process designed to foster public participation in supporting each participating nation's environmental laws. This article examines the outcomes to date of the citizen submission process, based on an analysis of the articles of the agreement and an examination of the rulings made on each case submitted under the citizen submission process. The analysis shows that CAFTA poses significant obstacles to citizen participation and has made minimal, if any, contributions to environmental law enforcement among the Parties to the agreement.